The ethical aspect in nursing education : a problem of lifestyle, of specific contents, and of cultural integration - Binetti, Paola (Medicina e Morale, 1997)
The new "Tabella XVIII ter" which has recently become effective, includes the syllabus of all the undergraduate courses linked to the Medical faculty in Italy. Compared to the previous "Tabella", it offers more space for the study of Bioethics both as a single and as a cross-subject and so becoming a landmark for all other courses. The study of Bioethics is to be found at the end of the course together with Health Law, Professional Ethics, and Applied Bioethics, it thus can find its cultural base in the study of Anthropology. This latter course is part of the second year Humanities studies, and of the third year History and Philosophy of Medicine course. The Libero Istituto Universitario - Campus Biomedico (Rome, Italy) educational proposal is to anticipate some of the first year course credits for History and Philosophy of Medicine in the early stages of students'educational project so as to increase their exposure to ethical problems. The main object is to make Bioethics and all its cultural implications the conceptual network to which Diploma Universitario per Infermieri (DUI) students can refer and so letting it become the real bearing structure of their education. Nowadays real innovation is possible only if nurses can refer to a context of ethical values which enables them to have a good relation with the sick person and his/her family. They will also be able to give coherent answers according to emerging needs and to carry out a high profile scientific research.